Looking beyond ESG preferences: The role of sustainable finance literacy in sustainable investing - Alix Auzepy; Christina E. Bannier; Florian Gärtner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
We assess how sustainable finance literacy affects people's sustainable investment behavior, using a pre-registered experiment. We find that an increase in sustainable finance literacy leads to a 4 to 5% increase in the probability of investing sustainably. This effect is moderated by sustainability preferences. In the absence of moderate sustainability preferences, any additional increase in sustainable finance literacy is at minimum irrelevant, and we find some evidence that it might even reduce sustainable investments. Our findings underscore the role of knowledge in shaping sustainable investment decisions, highlighting the importance of factors beyond sustainability preferences.
Keywords: G11; G18; G53; 330; Sustainable finance literacy; sustainable investments; behavioral finance; SFDR; MIFID